A perspectiva da inclusão de pessoas com deficiência nos cursos de formação de oficiais do Corpo de Bombeiros e da Polícia Militar do Maranhão - CHAHINI, Priscila Milena Costa (2024)
The research deals with the theme of the inclusion of people with disabilities in the Training Course for Officers of the Fire Brigade (CFO-BM) and the Military Police of Maranhão (CFO- PM), at the State University of Maranhão (UEMA). In order to discuss the topiche study started with bibliographical research on the context of the human rights of people with disabilities, specifically the process of inclusion of these people in higher education and the formal labor market, as well as the relationship between the two, based on authors such as Goldfarb (2009), Sassaki (2019), Rebelo (2008), Ribas (2011), among others. In this context, the research problem asks what are the main challenges to be overcome by people with disabilities in UEMA's Officer Training Courses for the Maranhão Fire Brigade and Military Police. In order to answer this problem, the main objective of this study is to analyze the main challenges to be overcome so that people with disabilities have the right to access, remain in and complete UEMA's Officer Training Courses for the Maranhão Fire Brigade and Military Police. In order to achieve the proposed objective, an exploratory, descriptive study was carried out with a qualitative approach. The data collection instruments included semi-structured interviews and questionnaires. The participants were 04 cadets with disabilities from the CFO-BM; 02 aspiring officers from the Fire Brigade, 10 cadets with disabilities from the CFO-PM and 08 professionals from the teaching and health areas of the Fire Brigade and Military Police of Maranhão. The research findings reveal that the BM and PM officer training courses are adjusting to issues involving the physical aptitudes of people with disabilities, their needs for specialized educational care and/or adjustments, their potential and vulnerabilities. Cadets with disabilities are bringing visibility to the human potential of people with disabilities. The main challenges to be overcome are the elimination of prejudice and ableism, as well as the lack of accessibility and attitudinal barriers. The inclusion of people with disabilities in the military has contributed to the deconstruction of exclusionary paradigms in relation to disability. There is still a long way to go, but the first step has already been taken, so let's wait for better outcomes.